2014
DOI: 10.1128/cvi.00688-13
|View full text |Cite
|
Sign up to set email alerts
|

Trained Immunity or Tolerance: Opposing Functional Programs Induced in Human Monocytes after Engagement of Various Pattern Recognition Receptors

Abstract: Upon priming with Candida albicans or with the fungal cell wall component β-glucan, monocytes respond with an increased cytokine production upon restimulation, a phenomenon termed “trained immunity.” In contrast, the prestimulation of monocytes with lipopolysaccharide has long been known to induce tolerance. Because the vast majority of commensal microorganisms belong to bacterial or viral phyla, we sought to systematically investigate the functional reprogramming of monocytes induced by the stimulation of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
344
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(369 citation statements)
references
References 52 publications
(77 reference statements)
16
344
4
5
Order By: Relevance
“…Similar protection has been observed in ischemia or endotoxin tolerance, in which preexposure to ischemia or lipopolysaccharide results in attenuated tissue injury during subsequent insults (23)(24)(25). The nature of the induced protection and underlying mechanisms of preconditioning are not yet clear, but studies suggest that innate immune cells such as monocytes/ macrophages play a central role (26)(27)(28). Here we found that the MSC preconditioning involved a distinct subset of suppressive MHC II + B220 + CD11b + monocytes/macrophages in the lung.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar protection has been observed in ischemia or endotoxin tolerance, in which preexposure to ischemia or lipopolysaccharide results in attenuated tissue injury during subsequent insults (23)(24)(25). The nature of the induced protection and underlying mechanisms of preconditioning are not yet clear, but studies suggest that innate immune cells such as monocytes/ macrophages play a central role (26)(27)(28). Here we found that the MSC preconditioning involved a distinct subset of suppressive MHC II + B220 + CD11b + monocytes/macrophages in the lung.…”
Section: Discussionsupporting
confidence: 55%
“…Recent studies showed that monocytes/macrophages can reprogram their responses toward immunogenic or tolerogenic phenotypes depending on the type and concentration of ligands they encountered, in the phenomenon termed "trained immunity and tolerance" (27,28). In this context, our study provides a possibility that MSCs use the plasticity of monocytes/macrophages and prime them to produce tolerance.…”
Section: Discussionmentioning
confidence: 82%
“…Strikingly, corresponding reactions could be also observed under in vivo conditions. Pretreatment of immunodeficient mice missing T-cells and Bcells (SCID) with BCG vaccine or β-glucan induced a significantly enhanced and sustained immune response (Ifrim et al 2014;Quintin et al 2014). The authors define the adaptive response of innate immune cells as "Trained immunity" and show strict dependence of the reprogramming of innate immune cells on the specific pathogen applied.…”
Section: Trained Immunitymentioning
confidence: 99%
“…For example, moderate to high doses of a variety of PAMP and PRR ligands, such as LPS (100 μg ml − 1 ), Pam3CSK4 (100 μg ml − 1 ), flagellin (10 μg ml − 1 ) and Poly(I:C) (100 μg ml − 1 ) (which all engage TLRs) induced heterogeneous tolerance in human monocytes. 34 Lower doses (0.1 pg ml − 1 to 1 μg ml − 1 ) however, induced heterogeneous training. In contrast, low to moderate doses of β-glucan (1 μg ml − 1 ), Tri-DAP (10 μg ml − 1 ) and muramyl dipeptide (10 μg ml − 1 ) (which engage NODs), all induced training (up to fivefold increases in TNF-α).…”
Section: Trained Innate Immunitymentioning
confidence: 99%
“…For example, whilst high-dose LPS results in decreased production of proinflammatory molecules upon re-exposure to LPS, low-dose LPS exposure results in increase production of proinflammatory molecules upon re-exposure to LPS. 34 That this memory effect is heterogeneous and long lasting has important implications, as it may set the stage for a proinflammatory responsive state in response to a diverse array of temporally distant immunostimulatory events. Table 1 lists some of the main features of trained innate immunity, as well as potential consequences for neuropsychiatric disorders.…”
Section: Trained Innate Immunitymentioning
confidence: 99%